Economic Diversification in the Gulf Countries: Challenges and Future Prospects (Revue El-Wahat pour les Recherches et les Etudes, 2026)
The economic situation in the Gulf region highlights the urgent need for an economic diversification strategy to address the risks associated with international market fluctuations.  The oil markets have experienced multiple price crises since the 1980s, the most recent beginning in the middle of 2014. As a result, some Gulf nations have experienced their first budget deficits, necessitating both internal and external borrowing, a withdrawal from international reserves, and the implementation of austerity measures. As a direct consequence of this, there has been a decrease in subsidies for essential goods and fuel, necessitating citizens to navigate significant economic changes. While not all industries must contribute equally to GDP, it is essential to make efficient use of both domestic and international resources. By encouraging the growth of new sectors that take in capital and labor, encouraging trade, and activating the banking sector, this strategy has the potential to reduce reliance on any one sector or commodity.